Ultimate 3D game engine design and architecture. - Sherrod, Allen, ....- (Boston : Charles River, 2007)
"Ultimate 3D Game Engine Design and Architecture" is a complete reference for designing and creating a game engine from the ground up. The book covers the various systems and processes that go into a complete game engine, with an emphasis on the issues to consider when designing the architecture for the engine. Unlike other books that only focus on one aspect of the game engine, such as graphics or physics, this book focuses on a complete game engine from a cross-platform perspective. The depth of coverage this book provides gives programmers aspiring to get into game development and experienced game developers all the details they need to create a complete game engine, a sample of which is on the companion CD-ROM. Contents:PART I INTRODUCTION TO GAME ENGINES 1 Introduction to Game Engines 2 Engine Core 3 Input, Sound, and Networking PART II GRAPHICS AND ENVIRONMENTS 4 Rendering Systems 5 Rendering Scenes and Scene Graphs PART III PHYSICS, AI, AND SCRIPTING 6 Physics 7 Artificial Intelligence 8 Scripting PART IV DEMOS 9 Game Demos PART V GAME OVER 10 Conclusions
Keywords: Computerspelen